2013
DOI: 10.1007/s00414-013-0867-y
|View full text |Cite
|
Sign up to set email alerts
|

The new guidelines for paternity analysis in Germany—how many STR loci are necessary when investigating duo cases?

Abstract: The requirements in the new German guidelines for paternity analysis have not only changed according to the so-called Gendiagnostikgesetz, the new German law regulating human genetic as well as paternity analyses, but also regarding the minimal number of short tandem repeats (STRs) which should be investigated (15 STRs) and the minimal required average exclusion chance (99.999 %). Even in paternity analyses involving only two people (e.g., father and child or mother and child), this exclusion chance is mandato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The likelihood of the simulated/observed genotype data of the pairs was then calculated under three different hypotheses about their relationship (full sibs, half sibs, and unrelated). Likelihood ratios and W-values were calculated for pairs of the three hypotheses using frequency data from our own study of unrelated Germans [13].…”
Section: Simulation Of Datamentioning
confidence: 99%
See 3 more Smart Citations
“…The likelihood of the simulated/observed genotype data of the pairs was then calculated under three different hypotheses about their relationship (full sibs, half sibs, and unrelated). Likelihood ratios and W-values were calculated for pairs of the three hypotheses using frequency data from our own study of unrelated Germans [13].…”
Section: Simulation Of Datamentioning
confidence: 99%
“…Table 7 Results for calculating full sibship versus unrelated from 112 pairs of unrelated people in comparison to simulated data. Calculations were done using German population frequencies [13] …”
Section: Scenario 3: Full Siblings/half Siblingsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this sense, Poetsch et al (2013) concluded that the number of hypervariable loci available for a genetic linkage analysis is directly associated with the percentage of certainty established during the assessment of the analysis (Børsting et al, 2008;Rodovalho et al, 2015;Zhang et al, 2015). Therefore, it is critical that STR panels provide sufficient security, permitting an accurate and unfailing conclusion regarding the genetic linkage analysis.…”
Section: Introductionmentioning
confidence: 99%